Institutional Ownership's Moderating Role on the Impact of Debt Costs, Corporate Social Responsibility, and Earnings Management on Tax Avoidance - Tsaltsah Hanifah Ardhy; Maryati (E-Jurnal Akuntansi, 2025)
This study examines the determinants of tax avoidance, focusing on debt costs, corporate social responsibility, and earnings management, with institutional ownership as a moderating variable. Employing a quantitative research approach, the study draws its sample from mining sector companies listed on the Indonesia Stock Exchange between 2019 and 2023. Using a purposive sampling technique, 32 companies were selected for analysis. The study applies Moderated Regression Analysis (MRA) to assess the relationships among the variables. The findings indicate that debt costs, earnings management, and institutional ownership significantly influence tax avoidance, whereas corporate social responsibility does not have a significant moderates the relationship between debt costs and earnings management on tax avoidance but does not moderate the effect of corporate social responsibility on tax avoidance.